Human and elephant conflict in Lower Kinabatangan, Sabah - Lee, Shan Khee (2002)
The seasonal movements of elephants and the socio-economic impacts of damage in cultivated areas in Lower Kinabatangan were studied from January 1999 to August 2000 so as to identify a "win-win" resolution to reduce the conflicts between humans and elephants. The elephants in Lower Kinabatangan are isolated into two populations, one population occurring west of Bukit Garam, which was not studied, while the study population occurs between the villages of Batu Putih and Abai in the Lower Kinabatangan Wildlife Sanctuary (LKWS). Approximately 80 elephants have been observed within 318.37 km2 in LKWS. One intensively studied family group (Maturup) was successfully tracked for 153 days between August 1999 and August 2000. The rate of elephant deaths detected in the Lower Kinabatangan due to human-elephant conflict was estimated as 0.91 individuals per year, and there were no cases of human death due to elephants in the region so far. The average number of cases of crop raiding in the Lower Kinabatangan was estimated as 10.82 ± 5.25 cases per year throughout the period from 1990 to 2000. Raiding frequency reached a peak during January-March, which is the wet season and immediate post-wet season. The total cost of damage by elephants within the 20 months of the study period was estimated as RM 478,400.50. The reported group size of problem elephants that raided crops varied from one to more than 40 individuals. Oil palm was the most frequently raided (92.64%) of all raided crops. The minor crops that have been raided were paddy (3.02%), banana (2.19%), maize (1.33%), coconut (0.68%) and minor fruits (0.14%). The results suggested that 55.56% of damage by elephants was upon oil palm trees below the age of two years old. The damage decreased with the increasing age of trees, and no trees aged seven or more were raided. Batu Putih was the village with the highest levels of conflict (52.63% of cases), followed by Sukau (26.32%), Billit (15.7%) and Abai (5.26%). Some 39% of oil palm plantations (n=8) were presently having power fencing as a mitigation method. The most effective mitigation method used throughout estates in the region was considered to be bright lights (40.74%); while the most common and traditional method used in villages was sound (59.37%). There were 21 families and 46 species of plants collected and identified as elephants' foods, with Graminae, Maranthaceae and Zingiberaceae being the three major plant families consumed. The most conventional 'win-win' solution recommended is in-situ conservation of elephants in LKWS, with mitigation measures such as fencing to maintain the elephants within the sanctuary.